2005
DOI: 10.1074/jbc.m501492200
|View full text |Cite
|
Sign up to set email alerts
|

Direct Binding to Ceramide Activates Protein Kinase Cζ before the Formation of a Pro-apoptotic Complex with PAR-4 in Differentiating Stem Cells

Abstract: We have reported that ceramide mediates binding of atypical protein kinase C (PKC) to its inhibitor protein, PAR-4 (prostate apoptosis response-4), thereby inducing apoptosis in differentiating embryonic stem cells. Using a novel method of lipid vesicle-mediated affinity chromatography, we showed here that endogenous ceramide binds directly to the PKC⅐PAR-4 complex. Ceramide and its analogs activated PKC prior to binding to PAR-4, as determined by increased levels of phosphorylated PKC and glycogen synthase ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
181
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(192 citation statements)
references
References 59 publications
9
181
1
1
Order By: Relevance
“…PKC-immune complex kinase assays have been commonly used to monitor PKC-activity (12,39,49,58). As demonstrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PKC-immune complex kinase assays have been commonly used to monitor PKC-activity (12,39,49,58). As demonstrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, atypical PKCs are regulated by phosphatidylinositol 3,4,5-trisphosphate produced by phosphatidylinositol (PI)3-kinase, ceramide, and by other proteins (20,49,58). PI3 kinase phosphorylates the D-3 position of the inositol ring of phosphoinositides, recruiting proteins with pleckstrin homology domains to membranes, such as PKB/kt and PKC-/ .…”
mentioning
confidence: 99%
“…In Vitro Lipid-Protein Polarity Complex-The in vitro reconstitution of a lipid-protein polarity complex was performed following the LIMAC (lipid vesicle-mediated affinity chromatography) procedure as published previously (5). In brief, phosphatidylserine (PS, 420 g) and C 16 -ceramide (107 g) were dried from organic solvent and resuspended under sonication in 500 l of buffer (50 mM Tris/HCl, pH 7.5, 150 mM NaCl).…”
Section: Es Cell Differentiation Protocol and Quantification Of Propermentioning
confidence: 99%
“…Our studies have shown that the membrane sphingolipid ceramide regulates apoptosis during embryonic stem (ES) 3 cell differentiation (1)(2)(3)(4)(5). This regulation is initiated by direct physical interaction of ceramide with atypical PKC or (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation